Emotional intelligence in teaching: a key to performance and institutional climate in basic education - Maraza-Quispe, Benjamin; Rosas-Iman, Victor Hugo; Feliciano-Yucra, Giuliana; Martinez-Lopez, Atilio Cesar; Ortiz-Corimaya, Elizabeth Katherine; Choquehuanca-Quispe, Walter; Coasaca-Hancco, Frida Karina; Nuñez-Saavedra, Luis Elfer (Institute of Advanced Engineering and Science, 2025)
This study addresses the lack of understanding regarding the relationship between emotional intelligence (EI), teaching performance, and institutional climate (IC) in basic education. As a solution, the study proposes evaluating and strengthening teachers’ EI to enhance both their performance and the school environment. Using a quantitative, non-experimental, correlational design, the research analyzed a randomly selected sample of 145 teachers. Validated questionnaires measured dimensions such as self-awareness, self-regulation, motivation, empathy, and social skills, as well as teaching preparation and IC. The results reveal significant positive correlations between EI and IC (r=0.85) and between teaching performance and IC (r=0.78). This suggests that higher EI not only improves teaching effectiveness but also fosters a positive institutional environment. The study concludes that enhancing teachers’ EI can optimize both their performance and institutional dynamics, contributing to higher-quality education. The findings support the implementation of EI training programs as a key strategy to improve teaching performance and the school climate (SC).